O desenvolvimento profissional docente na voz dos professores alfabetizadores - Pascotto, Alessandra Daniele [UNESP] (2014)
This dissertation focuses on the issue of Teacher Professionalism. Presents research on the approaches given by literacy teachers, their initial training and contributions to building their teaching knowledge (theoretical and practical).With the purpose of providing grants for public policies for teacher education, this study analyzes how important the initial and continuing training for literacy teachers. Participated in the survey in 2013, 39 teachers, one from each school, which corresponds to approximately 30% of effective literacy teachers, who taught in the 1st year of elementary school in public schools in a city in the state of São Paulo. The instruments used for data collection are: semi-structured, recorded and transcribed individual interviews and analysis of documents relating to continuing education activities offered to literacy by the Municipal Secretary of Education for the period 2010 to 2013. In 2010, work began on the deployment in the city of Elementary School 9 years according to official regulations. The data obtained are analyzed in the light of the theoretical contributions of authors such as Micotti (1998, 2004, 2009, 2012), Tardif (2002, 2006), Tardif and Lessard (1998); Schon (1983); Gatti (2009) and others, involving discussion and reflection about the professionalization of the teaching profession, the professional development of teachers and the construction of teaching knowledge, in particular knowledge needed to literacy teacher. The results indicate that literacy teachers while acknowledging the importance of initial training it is insufficient for the practice of teaching, particularly in relation to the teaching of theoretical and practical knowledge related to the teaching and learning of literacy. Reaffirm the results of previous research to show that when this main source of knowledge of the construction of the teaching practices ... (Complete abstract electronic access below)